Amalan kepimpinan autentik guru besar dan komitmen guru sekolah rendah program transformasi sekolah 2025 (TS25) Daerah Kluang, Johor - Mohamad @ Md. Nor, Azleeana (2021)
The School Transformation Program 2025 (TS25) is an initiative of the Ministry of Education Malaysia to increase student success in schools through effective leadership, competent teachers and strong commitment of the Parent-Teacher Association (PIBG). However, at the same time, the literature review shows that the percentage of teachers’ commitment of some schools in Malaysia is still at moderate level. The causes of decreasing teacher commitment in school include of one-way communication, interpersonal relationship and weak leadership style among administrators toward the organization. Therefore, this study aims to identify and discusses findings the practice of leadership authentic among headteachers' and its relationship with teachers’ commitment in twelve schools involved with the School Transformation Program 2025 (TS25) in Kluang District, Johor. The level of authentic leadership practices of headteachers' were investigated from the aspects of four main dimensions which are dimension of self-awareness, dimension of balance process information, dimension of appreciation of moral values and also the dimension of transparency in the teacher's commitment. A descriptive quantitative study and involved 104 respondents from twelve Primary School Transformation Program 2025 (TS25) in Kluang, Johor selected through the stratified sampling technique. This study using questionnaires as research instrument. The findings are analyzed using Statistical Package for Social Science (SPSS) software version 26.0. Descriptive statistics such as frequency, percentage, standard deviation and mean score are used to look at the respondent's profile distribution, the level of authentic leadership practices of headteachers' and the level of teacher commitment in primary school of TS25. The results showed that all the headteachers' studied practiced the four dimensions of authentic leadership at a moderate level (mean=3.51) where the dimensions of appreciation of moral values (mean=3.54) are most often practiced. The study also found that the teachers' commitment under the headmaster's leadership was at a low level (mean=1.98). In addition, data analysis also found the relationship between authentic leadership and commitment is positive and at a low level.